THE LABOR OF PRISONERS IN INTERNAL WORK IN CORRECTIONAL INSTITUTIONS OF THE SMOLENSK, BRYANSK AND ORYOL PROVINCES IN THE 1920S - Yankovich P.V. (Вестник Брянского государственного университета)
The article provides a detailed examination of the labor activities of prisoners engaged in internal work within correctional institutions located in the Smolensk, Bryansk, and Oryol provinces during the 1920s. Particular attention is given to the primary types of work in which the incarcerated individuals were involved, as well as the conditions of labor and levels of productivity. This historical period represents a significant stage in the development of the penitentiary system in Russia and is of particular interest for study in the contemporary context, especially as the corrections system undergoes considerable changes and reforms. During the 1920s, our country experienced radical reforms in the penal sphere aimed at improving the conditions of prisoner confinement and optimizing their labor activities. At that time, these ideas were pioneering not only for Russia but also for Europe as a whole. The Soviet authorities, during the period under consideration, began to formulate a new penitentiary policy based on the principle of corrective-labor functioning within correctional institutions. This process of reform and paradigm shift in the operations of these institutions represents a unique experience in our national history and may serve as a valuable reference for contemporary transformations of the Russian penitentiary system and its future development.